Repatriantki z Wołynia pionierkami hafciarskiej tradycji wynalezionej na Pomorzu - Angutek, Dorota (1963- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The gist of the article is to describe the genesis of embroidery tradition that was created and pupularized three women repatriated from Volhynia after the II World War into small town Więcbork in the middle of Pomerania. They was Zofia Cybulska, Wanda Kinda and Irena Cichończyk who has been lived in Więcbork till now. The first ones of the women carried out embroidery from Złotów to Więcbork where that had not been ever occured before. The proces of rising this tradition in Więcbork, and wider Sępólno Krajeńskie district is elaborated in the article in detailes.
Keywords: repatriantki; Wołyń; Krajna; haft krajeński; tradycja wynaleziona; repatriant women; Volhynia; Krajna embroidery; invented tradition